Neurodevelopment Outcome of Neonates Treated With Intraventricular Colistin for Ventriculitis Caused by Multiple Drug-Resistant Pathogens—A Case Series - Hussain, Kashif; Sohail Salat, Muhammad; Ambreen, Gul; Iqbal, Javaid (Frontiers in Pediatrics, 2021)
Background: Multiple-drugs resistant-Gram negative bacteria (MDR-GNB) associated neonatal ventriculitis is a life-threatening complication that needs timely diagnosis and effective treatment with broad-spectrum antimicrobials in critical care settings. Inadequate penetration of antibiotics through the blood-brain barrier also demands an intraventricular (IVT) route of administration. This study is reporting mortality and neurodevelopmental sequelae of neonates till 18 months of age, who received IVT-colistin for treating MDR-GNB associated ventriculitis. Methods: In a case series of seven neonates with ventriculitis due to MDR-GNB at NICU of Aga Khan University Hospital, Pakistan, between June 2015-2018, we reviewed IVT-colistin therapy in critically ill neonates. Treatment outcomes were assessed based on clinical sign’s resolution and MDR-GNB eradication in subsequent CSF cultures. Neurodevelopmental outcomes were evaluated at 18-months after discharge. Results: The average birth weight was 1.38 kg (range:1.02-1.5 kg) and the average gestational age was 30.7 weeks (ranged:26-34 weeks). All neonates reported colistin sensitive MDR-GNB in CSF, 5 with Acinetobacter baumannii, and polymicrobial CNS infection was found in 2 patients (1 due to Klebsiella pneumonia and A. baumannii and 1 due to K. pneumonia and Escherichia coli). All neonates received IVT colistin and concomitant intravenous meropenem and 5 of them also received intravenous colistin. One neonate died. At the 18-month assessment, only one neonate had cerebral palsy and hydrocephaly and 50% had seizure disorders. Conclusion: Practicing intraventricular antibiotics in the neonatal population is challenging but may be used successfully, especially to overcome the limitation of poor penetration through the blood-brain barrier.